Odpowiedzi

2010-02-22T14:52:49+01:00
A)7x3 - 3x2= x2 (7x-3)
(-2)2 [7*(-2) - 3]= 4(-17) = -68
b) 3x2 + 6ax = 3x(x+2a)

nie jest w pelni napisane ile wynosza x i a ale tylko podstaw i Ci wyjdzie
c)5ab - 10a2b + 15ab2
5ab(1-2a+3b)
5*(-1)*2 (1-2*(-1)+3*2)
-10 * ( 1+2+6) = -10 +10 = 0
2010-02-22T15:07:36+01:00
A) 7x3-3x2 dla x=-2
x2(7x-3)
7*(-2)3-3*(-2)2
7*(-8)-3*4
56-12
44
b)3x2+6ax dla x= ; a=
3x(x+2a)

c)5ab-10a2b+15ab2 dla a= -1, b=2
5ab(1-2a+3b)
5*(-1)*2-10*(-1)2*2+15(-1)*2*2 (ta ostatnia dwójka to do kwadratu ma być)
10-20+60
30